Associations of Cardiovascular Risk Factors and Genetic Markers with Development of Arterial Hypertension in the Population of Mountain Shoriya - T. A. Mulerova; S. A. Maksimov; M. Yu. Ogarkov; O. V. Gruzdeva; A. V. Ponasenko; V. N. Maksimov; M. I. Voyevoda; E. S. Filimonov; G. V. Artamonova (Рациональная фармакотерапия в кардиологии)
Aim. To study the combined effect of cardiovascular risk factors and genetic markers that encode the proteins of the main components of neurophysiological systems (renin-angiotensin-aldosterone, sympathetic-adrenal systems, endothelial dysfunction) on the development of arterial hypertension among the indigenous and non-indigenous population of Mountain Shoriya.Material and methods. We performed a clinical and  epidemiological study  of the compactly settled population in the remote areas  of Mountain Shoriya. This region of middle mountains is situated in the south of Western Siberia. We examined 1409 subjects (901 subjects – the representatives of indigenous nationality [the Shors], 508 subjects – representatives of non-indigenous nationality [90% among them  were the representatives of the European ethnicity]). Hypertension was diagnosed according to the National Guidelines of the Russian Society of Cardiology/the Russian Medical Society on Arterial Hypertension (2010). All patients underwent clinical, laboratory and  instrumental investigation. Polymorphisms of genes  ACE (I/D, rs 4340), АGT (c.803T>C, rs699), AGTR1 (А1166С, rs5186), ADRB1 (с.145A>G, Ser49Gly, rs1801252), ADRA2B (I/D, rs 28365031), MTHFR (c.677С>Т, Ala222Val, rs1801133) and NOS3 (VNTR, 4b/4a) were tested using polymerase chain reaction.Results. Cardiovascular risk factors  associated with hypertension in cohort  of Shorians: hypercholesterolemia [Odds Ratio (OR) 1.54,  low density lipoproteinemia (OR 1.48), violation of carbohydrate metabolism (OR 1.53), obesity (OR 2.25), including its abdominal type (OR 1.53), the family anamnesis of early cardiovascular diseases (OR 1.88)]  and  rs4340 polymorphisms of the  ACE gene  (OR 4.39), rs5186 of the  AGTR1 gene  (OR 10.02); in the cohort of the non-indigenous ethnos – hypercholesterolemia (OR 1.87), hypertriglyceridemia (OR 1.87), obesity (OR 2.75), abdominal obesity (OR 2.73), family anamnesis of early cardiovascular diseases (OR 2.48), the polymorphism rs5186 of the AGTR1 gene (OR 26.77). Genotype G/G ADRB1 gene was characterized by protective effect against hypertension in the Shorians.Conclusion. Evaluation of the complex influence of clinical and genetic factors  on the development of hypertension in the population of Mountain Shoriya showed their comparable importance among the indigenous population and  the predominance of non-genetic factors  among the non-indigenous population.